The other Jesus : stories from world religions - Outcalt, Todd. (Lanham : Rowman & Littlefield, 2014)
We're familiar with the Jesus portrayed in the New Testament, but many people are surprised to learn that a wealth of stories and traditions about Jesus have always existed alongside the usual Biblical sources. Judaism, Islam, and Buddhism -- among other religions -- have created their own tales about Jesus, sometimes out of necessary self-preservation and reaction to the claims of the church, but more often through thoughtful and artistic adaptation. The Other Jesus explores these varied traditions and offers a fresh exploration of Jesus -- new perspectives that challenge long-accepted beliefs about his place in history and his impact on other religions.
The word made flesh: The Jesus of the early church -- The Jewish Jesus: Yeshuah and the rabbis -- The church speaks: Jesus and alternative communities -- Isa and Muhammad: The Jesus of Islam -- "The Jesus of the soul": Understanding the Sufi Jesus -- From the far east: Jesus in Taoism and Buddhism -- Jesus as they saw Him: Images and ideas of Christ throughout history -- Appendix: Chronological list of Jesus traditions and writings.
Includes bibliographical references (pages 233-235) and index.
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Words -- Extra-canonical parallels; Bible. -- Extra-canonical parallels; Christianity and other religions